2006
DOI: 10.1309/6h0a-rqf7-k3y6-08eh
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies Immunoreactive With Formalin-Fixed Tissue Antigens Recognize Linear Protein Epitopes

Abstract: It is not clearly understood why some monoclonal antibodies bind to their antigens informalin-fixed, paraffin-embedded tissue sections but others do not. To address this question, we analyzed the protein epitopes of 9 monoclonal antibodies that are immunoreactive after formalin fixation and antigen retrieval. We identified the antibody contact sites by using phage display and synthesized corresponding peptides derived from the GenBank database sequence that contain the predicted antibody binding sites. Our dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 0 publications
2
39
0
Order By: Relevance
“…The reduction of cross-linking accompanies fixation. These conclusions are supported further by the work of Sompuram et al who demonstrated both that antibodies reacted with linear epitopes and that the presence of an irrelevant protein positioned to block access of the primary antibody to the reactive epitope reduced immunoreactivity (Sompuram et al 2004(Sompuram et al , 2006a(Sompuram et al , 2006b). …”
Section: Effects Of Fixation On Intraand Intermolecular Cross-linkingmentioning
confidence: 65%
“…The reduction of cross-linking accompanies fixation. These conclusions are supported further by the work of Sompuram et al who demonstrated both that antibodies reacted with linear epitopes and that the presence of an irrelevant protein positioned to block access of the primary antibody to the reactive epitope reduced immunoreactivity (Sompuram et al 2004(Sompuram et al , 2006a(Sompuram et al , 2006b). …”
Section: Effects Of Fixation On Intraand Intermolecular Cross-linkingmentioning
confidence: 65%
“…This cross -link is reversible upon heating at alkaline pH 21 . Lysine and cysteine can also form a cross -link at the ortho positions of the phenolic group of tyrosine through a Schiff -base intermediate.…”
Section: Reaction Of Formaldehyde With Proteinsmentioning
confidence: 97%
“…Instead, they support the model proposed by the Bogen laboratory, which suggests that antibodies chosen for their immunoreactivity for FFPE tissue sections recognize contiguous linear epitopes rather than the more common conformational epitopes. 21 Antibodies developed against denatured proteins are also likely to consist of paratopes that recognize short contiguous amino acid epitopes. 50 In this model, heat -induced AR is only required to regenerate and expose the primary amino acid sequence of the protein in order to restore immunoreactivity.…”
Section: Effect Of Formalin On the Secondary And Tertiary Structure Omentioning
confidence: 99%
“…The grid lines were superimposed after scanning the image to enhance clarity. Reproduced from Sompuram et al (2006b).…”
Section: Antibodies Useful In Formalin Fixed Paraffin Embedded (Ffpementioning
confidence: 99%